Improving Employee Performance through Empowering Leadership: Managing the Impact of Information Overload and Social Media Fatigue - Nastiti, Tur; Ratnawati, Shinta; Aman, Zainab Binti (MIX: JURNAL ILMIAH MANAJEMEN, 2025)
Objective: This study aims to analyse the effect of information and communication overload on social media fatigue, and its impact on employee performance, by considering the moderating role of empowering leadership.Methodology: This study uses a quantitative approach with a survey method and data collection through questionnaires distributed to permanent employees at universities in Indonesia. The data analysis technique uses linear regression and moderation test to test the relationship between variables.Findings: The results show that information and communication overload has a significant influence on social media fatigue, which in turn negatively impacts employee performance. Moreover, empowering leadership can mitigate such negative impacts, by providing support and autonomy to employees.Conclusion: The findings provide insights for organisations in designing more efficient communication policies and supporting empowering leadership development to improve employee well-being and performance in the digital age.